Sexualities, Identities and Bodies: Reducing the Vulnerability of HIV/AIDS Among Male Sex Workers in the Philippines - Hernandez, Laufred I. (Review of Women's Studies, 2004)
The purpose of this study was to explore the pagkatao of male sex workers in the Philippines and the ways sexual orientation, sex work and bodies are created, influenced, and modified based on the mindsets of the informants in the study (loob) and the nature of the discourse and practices that are manifested (labas). This study pointed to the fact that pagkatao of the male sex workers is socially constructed and is shaped by social, political, and economic influences, and modified throughout life. The loob (inside) and labas (outside) Filipino model aided in ascertaining the cultural meanings of sexuality that the participants in the study have structured in their minds and how these find utility in both oral and verbal languages that participants use. Analysis of the informants' oral narratives obtained during the interviews produced the overarching themes of sexual meanings, sexual relationships, perceptions on sex work, sexual and personal self-identification, and bodies. The multiplicity of sex workers' social sexual networks and the range of sexual practices they engage in make it difficult to ascertain their pagkatao; there are marked incongruences between the social constructions of male sexuality and the realities of these men's sexual experiences.